Evaluation of strategies for increasing response rates to postal questionnaires in quality control of nasal septal surgery - Merete T. Egeland; Magnus Tarangen; Olga Shiryaeva; Caryl Gay; Liv K. Døsen; Rolf Haye (BMC Research Notes, 2017)
Abstract Background Postal questionnaires are often used to assess the results of nasal septoplasty, but response rates vary widely. This study assesses strategies designed to increase the response rate. Methods Postoperative questionnaires using visual analogue scales (VAS) for nasal obstruction were mailed to 160 consecutive patients alternately allocated to one of two groups. Group A received the questionnaire in the usual manner and group B received a modified cover letter with hand-written name and signature and a hand-stamped return envelope. Results Of the 80 patients in each group, 47 (58.8%) in group A and 54 (67.5%) in group B returned the questionnaire (p = 0.25). There were no age or gender differences between the groups, nor did the pre- and postoperative VAS scores differ between the groups. Conclusion The strategies used in this study increased the response rate to postal questionnaires by 8.7% points, but this was not a statistically significant or clinically meaningful improvement.